ANALISIS MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN IPA TERPADU SISWA KELAS VIII SMP NEGERI 6 SUSUA - Yustina Laia (Universitas Nias Raya, 2025)
The research aims to determine students' learning motivation in Integrated Science-Biology learning at SMP Negeri 6 Susua. The approach used in this research is a descriptive approach. This research data was analyzed using data reduction, verification and drawing conclusions. The results of this research concluded that what causes students' lack of motivation to learn is students' lack of attention to the subject matter (concentration), concentration is meant to focus all attention on the learning situation and lack of concentration can cause students to have difficulty learning. Lack of student participation and response when participating in teaching and learning activities (reaction). Reactions in learning activities require the involvement of physical and mental elements, as a form of reaction, so that learning must be active and students are slow in understanding the material (comprehension) and this results in low student learning outcomes. Suggestions for future researchers, the results of this research can be used as relevant research material.